2003
DOI: 10.1097/00007691-200302000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity Assessment of Carbamazepine-10,11-epoxide, Oxcarbazepine, and 10-Hydroxy-Carbazepine in Two Automated Carbamazepine Immunoassays: PETINIA and EMIT 2000

Abstract: This study was conducted to compare the cross-reactivity of two commercially available carbamazepine (CBZ) immunoassays (PETINIA and EMIT 2000) with carbamazepine-10,11-epoxide (CBZ-E), the active metabolite of CBZ. Oxcarbazepine (OCBZ) and its main metabolite 10-hydroxy-carbazepine (HCBZ) have a chemical structure closely related to that of CBZ. The cross-reactivities of these two drugs were also investigated. In the first part of the study, Lyphocheck blank human serum and Chemonitor quality controls (contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…CBZ is metabolized extensively in vivo. CBZE is the major metabolite that can be found in similar concentrations in serum as the parent compound and contributes to its biologic activity (Parant et al, 2003). CBZE was found in our studies to inhibit HDAC activity with the same potency as CBZ.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…CBZ is metabolized extensively in vivo. CBZE is the major metabolite that can be found in similar concentrations in serum as the parent compound and contributes to its biologic activity (Parant et al, 2003). CBZE was found in our studies to inhibit HDAC activity with the same potency as CBZ.…”
Section: Discussionsupporting
confidence: 55%
“…CBZE is the major metabolite of CBZ in vivo and is found in patients' serum at comparable concentrations as the parent compound (Parant et al, 2003). When preparing a 10 mM stock, we found that adding premixed HBC solution in H2O to CBZE powder yielded a suspension that was only partially active in our assays and formed a fine precipitate.…”
Section: Determination Of the Ic50 Of Hdac Inhibition By Cbz And Cbzementioning
confidence: 72%
“…In humans, more than 90% CBZE is subsequently metabolized by mEH to inactive CBZD after CBZ epoxidation [49,50]. The steady-state trough concentration of CBZE is 15-20% of the parent drug in CBZ monotherapy [51], and mEH plays the most important role in CBZE biotransformation and detoxication. CBZD:CBZE ratio is a more appropriate index for reflecting mEH activity in vivo than CBZ concentration.…”
Section: Discussionmentioning
confidence: 99%
“…18 It is also documented that valproic acid increases the incidence of carbamazepine-related toxic effects as well, due to accumulation of the epoxide metabolite in the plasma, despite total plasma carbamazepine concentrations within the therapeutic range. 14 The need for determination of carbamazepine and epoxide concentrations is clinically significant for select patient populations and clinical scenarios, wherein accumulation of the active epoxide level is likely. Although there are immunoassays that will cross-react with the epoxide metabolite to account for the amount of total active drug in circulation, there are currently no immunoassays for determination of the epoxide metabolite concentration independent of the carbamazepine concentration.…”
Section: Discussionmentioning
confidence: 99%